THE CORRELATION BETWEEN THE SCHOOL ADMINISTRATORS AND LINUS TEACHERS TOWARD THE IMPLEMENTATION OF LINUS PROGRAM IN SCHOOL - Hariana A. Ahong; Abdul Said Ambotang, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study was conducted to examine the relationship between the support of the school administrators and the contribution of LINUS teachers towards the implementation of the LINUS program in Kota Kinabalu district for primary school. A quantitative approach using a survey method was carried out in all the 53 primary schools in the district of Kota Kinabalu. The instrument that was used in the survey was a set of questionnaires, where data was collected for analysis and evaluation. The Statistical Package for Social Science (SPSS) was used for the data analysis. The findings of this study show that there is a strong connection between the supportive roles of the school administrator and the commitment of the LINUS teachers towards the implementation of the LINUS program in their respective schools.